Design Oriented STEM Education with Preschool Children - Yalçın, Vakkas; Erden, Şule (Southeast Asia Early Childhood Journal, 2023)
In this study, the effects of design-oriented STEM activities on preschool children were examined. In the research conducted with case study in qualitative research designs, 20 preschool children aged five years in a kindergarten formed the participants of the study. Design Oriented STEM Activities were completed with 24 sessions of 8 weeks, 3 days a week. Within the scope of the research, data were collected through observations, interviews and research diaries and content analysis was made. As a result of the analysis of the data, it was concluded that the applied design-oriented STEM education increased the problem-solving, communication and cooperation skills of the children, and that the STEM education process; It has been concluded that it raises the awareness of children and gives them a sense of responsibility. In addition, it has been concluded that STEM activities encourage children to solve problems and generate ideas, make permanent behavioral changes in children, and increase children’s social and adaptation skills.